Design of voice miner's lamp based on WiFi - WANG Fei (Gong-kuang zidonghua, 2022)
In order to solve the problem that most of the existing miner's lamps only have the functions of lighting, positioning, environment perception and so on, and do not have the voice intercom function, a voice miner's lamp with voice intercom function based on WiFi is designed. The voice miner's lamp takes industrial Ethernet ring network and WiFi network as transmission platform, and adopts VoIP voice communication technology so as to realize voice playback, audio acquisition, and intercom function with the dispatching center. The audio codec chip is used to realize the conversion of voice analog signal and digital signal, and UDP protocol is applied to transmit the signal to the dispatching center so as to complete the two-way transmission of voice data and realize the integration of voice intercom and miner’s lamp lighting. This paper introduces the key technologies of voice intercom function in details. Audio data encoding format and cache management, reliable voice data transmission mechanism are used to ensure the accuracy of voice playback. The low-power sleep technology of WiFi module and microcontroller STM32L151 are used to reduce the average current of the voice miner's lamp and extend the working time. The test results show that the voice miner's lamp can meet the demand of voice intercom between the dispatching center and the underground workers, the communication distance between the voice miner's lamp and the WiFi base station can reach 400 m, the intercom transmission delay between the voice miner's lamp and the dispatching center is less than 1 s, and the multicast transmission delay between the voice miner's lamps is less than 3 s. The average current of the voice miner's lamp is less than 70 mA during intercom, and the average current is less than 5 mA during idle time.